2023
DOI: 10.1021/acsomega.3c03656
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-QQQ-MS and RP-HPLC Detection of Bioactive Alizarin and Scopoletin Metabolites from Morinda citrifolia Root Extracts and Their Antitubercular, Antibacterial, and Antioxidant Activities

Pornpat Sam-ang,
Anuchit Phanumartwiwath,
Desy Liana
et al.

Abstract: Morinda citrifolia is a medicinal plant that has been traditionally used in various therapeutic applications. All parts of M. citrifolia including fruits, leaves, stems, roots, and flowers contain various biologically active phytochemicals. This study aimed to evaluate the antitubercular, antibacterial, and antioxidant activities of M. citrifolia root extracts and spectroscopically analyze the bioactive metabolites. M. citrifolia root extracts were prepared via maceration. The minimum inhibitory concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Its mechanism of action is interference in the synthesis of essential fungal cell components, disruption of cell walls and plasma membranes, and impairment of C. tropicalis biofilm growth, formation, and proliferation (Lemos et al, 2020). Recent studies have reported that scopoletin has strong antitubercular activity; the compound isolated from Morinda citrifolia roots exhibits high activity against Mycobacterium tuberculosis with an MIC of 50 μg/mL (Sam-Ang et al, 2023). The MIC of the crude ethanol extract from the stem bark of Hymenodictyon floribundum BL Rob.…”
Section: Pharmacological Activities Of Scopoletinmentioning
confidence: 99%
See 1 more Smart Citation
“…Its mechanism of action is interference in the synthesis of essential fungal cell components, disruption of cell walls and plasma membranes, and impairment of C. tropicalis biofilm growth, formation, and proliferation (Lemos et al, 2020). Recent studies have reported that scopoletin has strong antitubercular activity; the compound isolated from Morinda citrifolia roots exhibits high activity against Mycobacterium tuberculosis with an MIC of 50 μg/mL (Sam-Ang et al, 2023). The MIC of the crude ethanol extract from the stem bark of Hymenodictyon floribundum BL Rob.…”
Section: Pharmacological Activities Of Scopoletinmentioning
confidence: 99%
“…In addition, scopoletin shows antioxidant potential against DPPH (IC 50 = 0.82 mg/mL) and NO (IC 50 = 0.64 mg/mL) radicals (Sam-Ang et al, 2023).…”
Section: Anti-oxidant Activitymentioning
confidence: 99%
“…Moreover, the researchers created acylthiourea derivatives, including the production of a specific compound (23). Starting from compound (20), derived similarly to the method mentioned by Yu et al, [35] it underwent a reaction with oxalic dichloride in methylene dichloride, forming intermediate (21). The synthesis of compound (22) involved the reaction between intermediate (21) and ammonium sulfocyanate, using anhydrous ethanenitrile as the solvent.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Starting from compound (20), derived similarly to the method mentioned by Yu et al, [35] it underwent a reaction with oxalic dichloride in methylene dichloride, forming intermediate (21). The synthesis of compound (22) involved the reaction between intermediate (21) and ammonium sulfocyanate, using anhydrous ethanenitrile as the solvent. The final compound (23) was produced by reacting compound (22) with amine derivatives in the presence of anhydrous ethanenitrile.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation